Comparison between Split Dose and Single Dose Bowel Laxatives for Preparation of Colonoscopy in Patients with Bangladeshi Diets: A Randomized Clinical Trial - Rahman, Md Muhibur; Alam, Md Jahangir; Saha, Madhusudan; Chowdhury, Malay Kumar Sur; Ahmed, Mostak Uddin; Rahman, Muhammad Oliur (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Colonoscopy is an important diagnostic tool for colonic disease and its efficacy and safety have been correlated with adequate bowel preparation. This study compared the efficacy and tolerability of single-dose and split-dose sodium picosulfate lavage as a colon cleansing agent for colonoscopy preparation. Methods: This randomized clinical trial was conducted at the Department of Gastroenterology in Sylhet MAG Osmani Medical College Hospital, Sylhet, Bangladesh from June 2021 to May 2022.A total of 110 patients were selected by randomized sampling technique who underwent elective colonoscopy and were divided into split-dose (n=57) and single-dose (n=53) laxative groups. Bowel preparation was assessed by the Ottawa Bowel Preparation Scale (OBPS) and data were analyzed by SPSS 24.0. Result: The mean age of the patients was 47.4±17.7(SD) years in split-dose and 47.6±15.9 (SD) years in single-dose group. Both groups were statistically similar in terms of socio-demographic profile, medical history, clinical manifestation, and indication of colonoscopy (p>0.05). The mean of total OBPS score (4.39±2.0 vs 5.56±2.2, p=0.004) and caecal intubation time (6.60±3 vs 7.74±2.5, p=0.035) was lower significantly in split-dose than the single-dose group. However, colonoscopy findings, adverse events, and patient compliance were similar between groups (p>0.05). Conclusion: Split-dose is superior to single-dose bowel laxatives for colonoscopy preparation in terms of better mucosal cleanliness and lower caecal intubation time. However, further randomized controlled trial is recommended. J Bangladesh Coll Phys Surg 2024; 42: 329-335